The concept of an agroinfiltration kit for recombinant protein production for educational and commercial use—A journey through a forest of regulatory and legal implications - Spiegel, Holger; Nölke, Greta; Thangaraj, Harry; Schillberg, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
1. Abstract Recombinant expression using Agrobacterium-mediated transient transformation (ATT) of plants has developed into a robust and versatile method to rapidly produce proteins. The capability of plants to efficiently synthesize even homo- and hetero-multimeric complex folded proteins featuring disulfide bonds and other post-translational modifications such as N-linked glycosylation makes them superior to most of the established microbial, especially prokaryotic expression hosts. Compared to production in mammalian cell cultures, ATT requires lower skills, simple technical equipment and cheaper media components. Taken together these features make the method optimally suited for R&D applications involving the development and engineering of recombinant proteins for various purposes ranging from vaccine candidates, therapeutic proteins, towards enzymes for different pharmaceutical and technical applications. Despite these advantages the technology is currently not being used outside the community of plant research. The design and realization of a kit for educational and commercial use containing all the information, instructions and ideally also the material required to perform recombinant protein production using ATT was one of the objectives of the EU-funded Horizon 2020 project Pharma-Factory. While it is pretty straightforward to assemble a comprehensive instruction manual regarding the procedure itself, the clarification of regulatory and legal aspects associated with the provision, dissemination and use of the different materials and organisms required to perform ATT is a complex matter. In this article, we describe the initial concept of an ATT kit for educational and research and development (R&D) purposes and the specific regulatory and legal implications associated with the various kit components. We will cover aspects intellectual property rights, and freedom-to-operate (FTO) aspects, safety regulations for distributing genetically-modified organisms (GMOs), as well as export and import regulations. Our analysis revealed that important components of the ATT kit are freely available for research purposes but not or only with considerable effort for commercial use and distribution. We conclude with a number of considerations and requirements that need to be met in order to successfully disseminate such a kit in the future.